2008
DOI: 10.1111/j.1365-2036.2008.03685.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: glucocorticosteroids for alcoholic hepatitis – a Cochrane Hepato‐Biliary Group systematic review with meta‐analyses and trial sequential analyses of randomized clinical trials

Abstract: SUMMARY BackgroundGlucocorticosteroids versus placebo or no intervention for patients with alcoholic hepatitis have been evaluated for more than 35 years. However, the results of randomized trials and meta-analyses differ substantially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
107
2
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(122 citation statements)
references
References 38 publications
0
107
2
13
Order By: Relevance
“…While meta-analysis of several older, small trials of steroid therapy have shown short-term mortality benefit, its utilization remains controversial due to concern for infection development and the emergence of new literature challenging previous findings. 5,6,11 Along the same accord, a recent meta-analysis of pentoxifylline demonstrated a decreased incidence of fatal HRS but no short-term survival benefit compared to placebo. 12 Lack of survival benefit was most recently described by Thursz and colleagues in the STOPAH trial, which evaluated the effects of prednisolone and pentoxifylline therapy in 1103 severe AH patients with higher average MDF scores in the treatment group compared to our study (MDF = 63 in STOPAH vs. MDF = 42 in our study).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…While meta-analysis of several older, small trials of steroid therapy have shown short-term mortality benefit, its utilization remains controversial due to concern for infection development and the emergence of new literature challenging previous findings. 5,6,11 Along the same accord, a recent meta-analysis of pentoxifylline demonstrated a decreased incidence of fatal HRS but no short-term survival benefit compared to placebo. 12 Lack of survival benefit was most recently described by Thursz and colleagues in the STOPAH trial, which evaluated the effects of prednisolone and pentoxifylline therapy in 1103 severe AH patients with higher average MDF scores in the treatment group compared to our study (MDF = 63 in STOPAH vs. MDF = 42 in our study).…”
Section: Discussionmentioning
confidence: 67%
“…One hypothesis that has been proposed to explain higher mortality rates in patients with more severe disease is a ceiling effect of drug therapy in preventing the inflammatory cascade and ultimate liver damage. 2,5 Mendenhall and colleagues first described this phenomenon after observing that steroid treatment increased mortality in patients with an MDF > 54. 5 This cutoff should be further studied to determine if a true MDF range of treatment benefit exists before reaching a treatment ceiling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the current evidence does not support the use of steroids in AH and large low bias well designed RCTs are required. 7 Park et al 8 in a multicentre, open labelled noninferiority trial involving 124 patients with severe AH compared the short term mortality among the patients randomised to steroids or pentoxifylline. Patients were treated with either prednisolone 40 mg per day or pentoxifylline 1200 mg per day for 4 weeks.…”
Section: Commentsmentioning
confidence: 99%
“…However, the widespread utility of prednisolone, a corticosteroid with broad anti‐inflammatory and immunosuppressive actions, in improving survival outcomes in SAH remains controversial. From 1971 to 2014, there have been 13 randomized trials and four meta‐analyses that have investigated the use of corticosteroids in SAH 4, 5. In the main, these studies have indicated that steroids significantly increased the short‐term survival of patients with SAH, but concerns have revolved around the risk of sepsis and gastrointestinal hemorrhage.…”
mentioning
confidence: 99%